Miller's children: why giving teenage killers a second chance matters for all of us - Garbarino, James (University of California Press, 2018)
"Miller's Children is a comprehensive look at the consequences of the US Supreme Court's decision in the case of Miller v. Alabama, which outlawed mandatory life-without-parole sentences for juvenile murderers. This book describes the author's fieldwork as a psychological expert witness in more than forty resentencing cases of juveniles affected by the Miller decision (and follow-up rulings), providing a wide-ranging review of research on human development in adolescence and early adulthood. It focuses on how and why convicted teenage murderers have been able to accomplish dramatic rehabilitation and transformation, emphasizing the role of spiritual development, education, reflection, and mentoring in that process."--Provided by publisher